The senses in tourism: why is it important? - Ismail, Hairul Nizam (2015)
Man and nature are intertwined with human senses and their own experience towards the landscape around them. Particularly, in the tourism industries, sense play an important role as a motivation for visitors to travel themselves and to experience certain destinations and attractions in the visited places. However, previous studies on the sensory modes are biased on the concept of branding and images as the marketing strategy to promote the destination and less studies that focused on the experience quality through the sensory modes. So, on that basis, this paper aimed to review previous studies that involved sensory mode and it can be categorized into four main concepts, namely motivation and perception, brand and image, interpretation and engagement, and lastly, the experience quality, value and satisfaction of visitors.